Effect of aluminum oxide and silicon carbide abrasive type on stainless steel ground surface integrity - Mohd Syakir, Abdul Rahman (2010)
High surface qualities of stainless steel product are important because the applications of stainless steel are wide in industry such as food storage, surgery tools and many more. Grinding process can produce stainless steel product with high surface quality. Grinding is an abrasive machining process that can machine up to ±0.0025 mm tolerance. Grinding is also a surface finishing process that used to improve surface finish and tighten the tolerance of a product. This study focused on the determination of the effect of Aluminum Oxide and Silicon Carbide grinder wheel on the stainless steel surface integrity. Besides that, the relation of the depth of cut and the cutting fluid usage with the crack length and surface roughness are determined. Optimum parameter that contributes to the better surface roughness and less crack length observed. The interaction among them then investigated and analyzed using ANOVA. Mixed Taguchi design of experiments approach used since there are multiple factors of parameters with multiple levels. From the result, ANOVA analysis will be carried out. Experimental results show that coolant usage is optimum in reducing the surface roughness. The interaction of coolant with the depth of cut indicates that coolant can improve surface roughness and extend the level of depth of cut. Meanwhile, crack length and it tendency to occur are less when the depth of cut are less because less residual stress and heat generated. Surface integrity of grinded stainless steel with the Aluminum Oxide grinder wheel is better comparing with the Silicon Carbide grinder wheel. The grindability of stainless steel workpiece materials was found to increase substaintially by using the Aluminum Oxide grinder wheels.